PENGGUNAAN BEBERAPA PELARUT ORGANIK DALAM EKSTRAKSI BESI(III) DENGAN OKSIN SECARA EKSTRAKSI PELARUT - Devita, Liza (Sainstek : Jurnal Sains dan Teknologi, 2012)
The research on the extraction of iron (III)  aims at finding the best condition of extraction of iron (III) using oksin (8-hidroksikuinolin) as the complement. It was done by setting the  oksin concentration, pH, and the appropriate solvent. The  extraction process was done in a separating funnel. The reaction occurs when the water phase containing ions of iron (III) contacted an organic phase containing oksin as a chelate ligand. The water phase was measured with atomic absorption Spectrophotometer.  The concentration of iron (III) in the organic phase extracted was obtained from the difference between the concentration of iron (III) with the initial concentration of iron (III) which was measured by atomic absorption spectrophotometer. As the result of the research, it was found that Fe-Oksinat was extracted optimally at pH 3, the concentration of iron (III) concentration of 10 ppm and oksin 0.12 M, with a 40-minute standing time and agitation time 20 min. Fe-oksinat for benzene solvent extracted optimum pH 3, the concentration of iron (III) concentration of 10 ppm and 0.12 M. oksin with a 20-minute standing time and mixing time 10 minutes. From the comparative figures of the comparison distribution at the optimum conditions for the three solvents (chloroform, ethyl acetate and benzene), it was obtained that the best solvent for the extraction of iron (III) with oksin as a completing agent is chloroform. Key words : solvent extraction, organic solvents, oksin, Iron (III)